Study Literature Review On Returning Medical Record Documents Using HOT-FIT Method - Maisa Putra, Deni; Oktamianiza, Oktamianiza; Yuniar, Mega; Fadhila, Washi (Malikussaleh University, Aceh, Indonesia, 2021)
The return of medical record files is a system that is quite important in medical records, because the return of medical records starts from the file in the inpatient room until it returns to the medical record section in accordance with the return policy, which is 2x24 hours. The method used is a literature study with descriptive analysis which is done by describing the facts that exist then being analyzed, described, looking for similarities, views, and summaries of several studies. The results of the literature study show that humans are not responsible for returning medical record files, the organization lacks supervision from the management of returning files, technology (technology) with technology can assist in returning medical record files. So it is necessary to pay attention to the 3 components, so that it can produce a benefit (Net Benefit) from returning the medical record document. Based on the results of the study, it can be concluded that the factors that influence the return of medical record documents are in terms of the HOT-FIT method, (human) where the officers lack a sense of responsibility for medical record documents, and doctors and nurses do not pay attention to the form of filling out record documents medical records, so that it becomes an obstacle in returning medical record documents. It's good to have good supervision from the management.